Peranan Guru dan Pemanfaatan Teknologi dalam Pendidikan (Dampak Modernisasi dalam Pendidikan) - Risda Heldriyana; Firman Firman; Riska Ahmad (Universitas Islam Sumatera Utara, 2022)
Education cannot be separated from human life, and the era of development can never be separated from human life, so that these two things become inseparable, humans will continue to move forward and develop, accompanied by education, and will also continue to move forward with the times. One of the very rapid developments of the times is in the field of technology, where with its existence it brings convenience in the world of education, which used to be done only in class and at certain hours, now by utilizing technology in the field of education to facilitate the learning process teaching, education can be done anytime and anywhere, as long as the place is accessed by an internet network. This is of course very beneficial for the world of education and brings positive paths, but behind all the goodness, the use of technology in the teaching and learning process also brings negative paths, where technology will shift the role of the main teacher in education, and also cause the focus of student learning to be shifted to things - other interesting things that exist on the internet.